Popliteal Artery Entrapment Syndrome (PAES) in a 17-Year-Old Adolescent - Viktor Labmayr; Aryan Aliabadi; Kurt Tiesenhausen; Marianne Brodmann; Florian Schmid; Dana Moore (Case Reports in Vascular Medicine)
Introduction. Popliteal artery entrapment syndrome (PAES) is caused by compression of the popliteal artery (PA) due to deranged myotendinous structures. It can be asymptomatic or may present with exercise intolerance, claudication, or even limb-threatening ischemia. The clinical picture depends on the anatomy and degree of vascular compromise. Case Description. We report a case of a 17-year-old Caucasian male with PAES Type II presenting with intermittent claudication and progression towards acute limb ischemia. Diagnostics. MRI and MRA helped identifying the aberrant anatomy and thrombotic occlusion. Doppler ultrasound and conventional angiography have also been employed in a stepwise approach. Intervention. The thrombus at the site of occlusion was removed by the use of catheter-directed lysis. Subsequently, popliteal artery release was achieved by myotomy of the aberrant medial head of gastrocnemius muscle (MHGM) and muscle transfer to the medial femoral condyle. A three-month regimen of 60mg edoxaban was recommended after surgery. Outcome. Surgical correction of the anomalous anatomy and postoperative anticoagulation led to freedom of symptoms. Lesson. Clinical presentation of PAES mimicking peripheral artery occlusive disease is very rare but potentially limb-threatening. PAES should be considered in young and otherwise healthy individuals.